Unlocking Smart Data : Design Research into a Possible Smart Data Challenge Prize : Literature Review on Challenge Prizes.: Design Research into a Possible Smart Data Challenge Prize : Literature Review on Challenge Prizes. (2023) - Unknown
No abstract available